Enhancing the security of horizontal canal BPPV repositioning maneuvers: insights from virtual simulation - Li, Jianxin; Hu, Haoxiang; Zhang, Yihan; Yang, Xiaokai (Frontiers in Neurology, 2025)
Horizontal canal benign paroxysmal positional vertigo (hc-BPPV) presents distinct challenges in both diagnosis and treatment. This study aims to explore the trajectories of otoliths during different hc-BPPV reduction maneuvers using advanced virtual simulation technology, and evaluate the theoretical effectiveness and security of these maneuvers while providing recommendations for optimizing current techniques or developing innovative approaches. We created a high-fidelity, three-dimensional (3D) virtual model of the human vestibular system that accurately depicts the horizontal semicircular canal. Utilizing the Unity 3D platform combined with NVIDIA PhysX physics engines, and simulated various hc-BPPV repositioning maneuvers, including the Lempert roll, Gufoni maneuver, forced prolonged positioning, and Zuma maneuvering. The otoliths were modeled as spherical particles, with their motion trajectories analyzed through precise quaternion rotation. Then, we collected and examined the 3D trajectory, velocity, and positional changes of the otoliths in relation to key anatomical landmarks. The simulations indicate that traditional maneuvers such as Lempert and Gufoni are effective in repositioning otoliths, but along with the risk that otoliths mistakenly inserted into other semicircular canals. In contrast, Zuma maneuver is more complex to execute, but it provides higher security. The improved Zuma maneuver not only simplifies the procedure but also maintains high efficacy and security standards. This study provides a comprehensive comparison of various hc-BPPV repositioning maneuvers using virtual simulation technology. The modified Zuma maneuver is proposed as a more effective and safer treatment method. Further clinical validation and individual adjustment studies are necessary to optimize this approach and improve hc-BPPV management strategies.